Immunohistochemical Expression of the Alpha Nicotinic Acetylcholine Receptor 7 in the Human Normal, Diabetic, and Preeclamptic Placenta and Products of Conception - Alwazzan, Ahmad; Mehboob, Riffat; Gilani, Syed Amir; Hassan, Amber; Perveen, Shahida; Tanvir, Imrana; Waseem, Humaira; Ehsan, Kashifa; Ahmad, Fridoon Jawad; Akram, Javed (Frontiers in Physiology, 2020)
Preeclampsia (PE) and Gestational diabetes (GD) are complications in advanced pregnancy while miscarriage for early pregnancy. However, the etiological factors are not well understood. Smoking has been associated with these complications as well as the sudden intrauterine deaths, Sudden infant death, miscarriages and still births. However, the immunolocalization of alpha 7 nicotine acetylcholine receptor (α7-nAChR) is not studied. Materials and Methods: α7-nAChR subunit expression was evaluated in 10 paraffin embedded tissues placental tissues after full term normal pregnancy and 10 tissue samples of products of conception during first trimester by Immunohistochemistry. Among the placental tissues, 2 samples were normal placental tissue, 4 from PE mother and 4 from GD mother. The expression of α7-nAChR was compared between the 2 groups in general and within the sub-groups of placenta as well. Protein expression was evaluated using the nuclear labelling index (%) of villi with positive cells stained, positive cells in the decidua and intensity of staining in the outer villous trophoblast layer. Results: The expression of α7-nAChR protein was high in all the cases of placenta and POCs. α7-nAChR expression showed no notable differences among different cases of miscarriages irrespective of the mother’s age and gestational age at which the event occurred. However, there were some changes among the normal, PE and GD placental groups in the linings of the blood vessels. Changes were restricted to the villi (as opposed to the decidua) lining cells both cytotrophoblast and syncytiotrophoblast, and were specific to the α7 subunit. PE blood vessel lining were thicker and showed more expression of this receptor in endothelial cells and myofibroblasts in PE and GD groups. In POCs, the strong expression was observed in the decidua myocytes of maternal blood vessels and in syncytiotrophoblast and cytotrophoblast of chronic villi. Conclusion Nicotine acetyl choline receptors are found to be expressed highly in the placental tissues and in products of conception. They may be associated with the sudden perinatal deaths and miscarriages or complications of pregnancy.